Morphology and Karyotype of Two Frog Species from Irian Jaya - Rita Esterina (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to identify and compare the morphology and karyotype of Litoria caerulea and Litoria infrafrenata, which are useful as study materials to understand their patterns of relatedness and taxonomy. The results of this study indicate that the qualitative morphological characteristics of both frog species are different. Litoria caerulea has a chubby and short body with a distinctive feature of skin folds above the eyes that extend to the tympanum area, while Litoria infrafrenata has a slim and long body with a distinctive feature of a white line on the lower lip and along the front and hind limbs. And it was observed that the morphometry between the two frog species are significantly different (P ≤ 0.05).